Mental Disorders, Cognitive Impairment and the Risk of Suicide in Older Adults - Kułak-Bejda, Agnieszka; Bejda, Grzegorz; Waszkiewicz, Napoleon (Frontiers in Psychiatry, 2021)
More than 600 million people are aged 60 years and over are living in the world. The World Health Organization estimates that this number will double by 2025 to 2 billion older people Suicide among people over the age of 60 is one of the most acute problems. The factors which are strongly associated with suicide are mentioned: physical illnesses, such as cancer, neurologic disorder, pain, liver disease, genital disorders, or rheumatoid disorders. Moreover, neurologic diseases, especially stroke, may affect decision-making processes, cognitive capacity, and language deficit. In addition to dementia, the most common mental disorders are mood and anxiety disorders. A common symptom of these disorders in the elderly is cognitive impairment. The aim of this study was the present the relationship between cognitive impairment due to dementia, mood disorders and anxiety, and an increased risk of suicide among elderly people. Dementia is a disease where the risk of suicide is significant. Many studies demonstrated that older adults with dementia had an increased risk of suicide death compared to those without dementia. Similar conclusions apply to prodromal dementia Depression is also a disease with a high risk of suicide. Many researchers found that a higher level of depression was associated with suicide attempts as well as suicide ideation. Bipolar disorder is the second entity in the group of mood disorders with a high risk of suicide among the elderly. Apart from suicidal thoughts, bipolar disorder is characterized by high mortality. In the group of anxiety disorders, the greatest risk of suicide occurs when depression is present. In turn, suicide thoughts are more common in social phobia than in other anxiety disorders. Suicide among the elderly is a serious public health problem. There is a positive correlation between the occurrence of mental disorders such as dementia, depression, bipolar disorder, or anxiety and the prevalence of suicide in the elderly. Therefore, the elderly should be comprehensively provided with psychiatric and psychological support.